THE IMPACT OF THE PANDEMIC ON THE GLOBAL OIL AND GAS MARKET (Academicia Globe: Inderscience Research, 2022)
The coronavirus pandemic has had a significant impact on the global energy market. However, this impact is short-term. The most significant was the acceleration of the decarbonization process and the energy transition: the plans for the development of the energy industry in many developed countries include the intensification of investments and an increase in decarbonization costs. In the long term, this factor is negative for oil demand, neutral or positive for global gas demand.